Implementation of Anonymous social network (International Journal of Scientific Research and Management (IJSRM), 2024)
This paper describes a implementation of a server-client model that could be used as anonymous social network. It could be used for n clients. The anonymity of client is ensured on server side. The scheme implemented in this paper was proposed by Dr. Hamza Harkous and Dr. Rameez Rahman. The scheme was proposed for trusted users where users trust each other.